Proses dan Minat Belajar Mahasiswa dalam Pembelajaran Online di Era Pandemi Covid-19 - Rista Anggraini; Windy Sastri Febriana; Luluk Mufarohah; Indah Purnama Sari; Novianti Dinda Saputra; Idris - (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2021)
In the midst of the Covid-19 pandemic that spread outside in various countries, especially Indonesia, resulted in the government issuing policies on the transfer of learning, which initially occurred in a face-to-face into online learning at every level of education including universities. The purpose of this study is to analyze the process and interest of students in learning activities during the Covid-19 pandemic. This research uses a mixed method approach that is qualitative and quantitative. The study used online instruments distributed to 60 respondents. Respondents were taken from students of IPS Education, Malang State University. The steps in this study are (1) the formulation of problems, (2) finding the basis of theory, (3) formulation of research instruments, (4) distribution of research instruments, (5) presentation of data, and (6) drawing conclusions. The results of this study revealed that students of Social Science Education, Malang State University have a variety of methods used during the learning process ranging from using whasapp group, google classroom, sipejar, google meet, and zoom, for various reasons. The spirit in learning activities is also increasing, so that the knowledge gained during learning can be understood well.